Talent Management Practices and Employee Job Satisfaction in Nepalese Commercial Banks - Gautam, Kishor Kumar (KIC International Journal of Social Science and Management, 2023)
The primary objective of this study is to investigate the relationship between talent management practices and employee job satisfaction. The study employed a descriptive and analytical research design under the quantitative research method to achieve these objectives. The study targets all employees working in Nepalese commercial banks, including both headquarters and branch locations in Kathmandu, the capital city of Nepal, and a sample of 400 employees was selected. However, only 233 responses were received and used for further analysis. The selection of samples was done using a simple random sampling method. The study assessed the positions of different variables by calculating their mean values. The fitness of regression models was evaluated using F-values, and regression models were employed to examine the relationship between talent management practices and employee job satisfaction. The reliability of the data collection tool was tested using Cronbach's alpha value. Furthermore, regression assumptions were tested, including multicollinearity using tolerance and VIF value, and linearity using ANOVA. The results of the study indicate that talent management is a significant predictor of employee job satisfaction.